Leadership Styles of Principals and Job Satisfaction of Teachers in Abu Dhabi Public Schools: The Role of Organisational Commitment and National Culture - KADBEY, HANADI (2018)
The purpose of this study was to investigate the leadership style of principals and teachers’ job satisfaction in Abu Dhabi public schools and the relationship that exists between these variables. The study also examined the organisational commitment of teachers and its role as a mediator in the leadership style-job satisfaction relationship. Also, the study investigated the national culture dimensions of the principals and their links to the leadership styles that they adopt. The theoretical framework draws on The Full Range Leadership Theory of Bass and Avolio (1997), Herzberg’s Two Factor Theory (1959), Meyer and Allen’s (1991) three-dimensional model of organisational commitment and Dorfman and Howell’s (1988) revised Model of Hofstede. The study was conducted in 51 public schools in the Emirate of Abu Dhabi by employing a mixed methods explanatory sequential design. Four research questions were answered using quantitative and qualitative data collected from 51 Emirati principals and 438 Emirati teachers. Data cleaning, descriptive statistics and reliability statistics were run using IBM SPSS Statistics Version 22, and structural equation modelling was run using Mplus Version 7.0 software while thematic analysis was used to summarise qualitative data. The findings indicated that principals tend to be more transformational in their practices and that teachers tend to be more satisfied when their principals display transformational leadership practices and less satisfied when their principals practice the passive avoidant leadership. The intellectual stimulation and inspirational motivation of transformational leadership and the contingent reward of transactional leadership had positive significant relationships with job satisfaction while the laissez faire of passive avoidant leadership had a significant negative relationship. In addition, the affective dimension of organisational commitment was a significant mediator in some of the leadership styles-job satisfaction relationships. Furthermore, leadership styles and some of their dimensions were linked to all national culture dimensions with the exception of masculinity. Based on these findings, recommendations for educators and policy makers were provided and ideas for further research were identified to explore the topic of interest further.